Epilepsy mortality in Wales during COVID-19. (January 2022) - Daniels, Helen; Lacey, Arron S; Mikadze, David; Akbari, Ashley; Fonferko-Shadrach, Beata; Hollinghurst, Joe; Lyons, Ronan A; Rees, Mark I; Sawhney, Inder MS; Powell, Robert H; Kerr, Michael P; Pickrell, W Owen
Abstract: Purpose: The COVID-19 pandemic has increased mortality worldwide and those with chronic conditions may have been disproportionally affected. However, it is unknown whether the pandemic has changed mortality rates for people with epilepsy. We aimed to compare mortality rates in people with epilepsy in Wales during the pandemic with pre-pandemic rates. Methods: We performed a retrospective study using individual-level linked population-scale anonymised electronic health records. We identified deaths in people with epilepsy (DPWE), i.e. those with a diagnosis of epilepsy, and deaths associated with epilepsy (DAE), where epilepsy was recorded as a cause of death on death certificates. We compared death rates in 2020 with average rates in 2015–2019 using Poisson models to calculate death rate ratios. Results: There were 188 DAE and 628 DPWE in Wales in 2020 (death rates: 7.7/100, 000/year and 25.7/100, 000/year). The average rates for DAE and DPWE from 2015 to 2019 were 5.8/100, 000/year and 23.8/100, 000/year, respectively. Death rate ratios (2020 compared to 2015–2019) for DAE were 1.34 (95%CI 1.14–1.57, p <0.001) and for DPWE were 1.08 (0.99–1.17, p  = 0.09). The death rate ratios for non-COVID deaths (deaths without COVID mentioned on death certificates) for DAE were 1.17 (0.99–1.39, p  = 0.06) and for DPWE were 0.96 (0.87–1.05, p  = 0.37). Conclusions: The significant increase in DAE in Wales during 2020 could be explained by the direct effect of COVID-19 infection. Non-COVID-19 deaths have not increased significantly but further work is needed to assess the longer-term impact.